Thermally Induced Electromagnetic Fluctuations by Protons and Alpha Particles in the Solar Wind - Rafael O. Medina; Benjamin Toledo; Roberto E. Navarro; Juan A. Valdivia (The Astrophysical Journal)
We present an initial study on the contribution of alpha particles, alongside electrons and protons, to the generation of thermally induced electromagnetic fluctuations (TIEFs) in space plasmas, such as the solar wind. The inclusion of alpha particles is anticipated to influence the regulation of the quasi-stable region in the beta-anisotropy diagram for both ion species, as well as the amplitude of the fluctuations. For this analysis, we filtered 30 yr of solar wind data at 1 au, focusing on conditions close to isotropy for protons and alpha particles, given that the observational distribution peaks near this state. The filtered data are displayed and organized in the ( β _∥ _p , β _∥ _α ) plane, where β _∥ denotes the ratio of parallel plasma pressure to magnetic pressure for protons ( p ) and alpha particles ( α ). In this plane, we analyze the ratio of alpha particle to proton density, n _α / n _p , the squared perpendicular magnetic fluctuations, and compressibility. Furthermore, we compare these magnetic fluctuations with the total fluctuating magnetic energy density derived from a generalized fluctuation–dissipation theorem, highlighting a clear similarity. We also present Fourier spectra for a subset of the data and the corresponding theoretical curve predicted by TIEFs. This study suggests that TIEFs may play a significant role in explaining the unexpected fluctuations observed in space plasmas. Additionally, it provides preliminary evidence that the inclusion of additional ion species could serve as a quantitative test for the theoretical models proposed to describe these fluctuations.